2023
DOI: 10.1093/evlett/qrac005
|View full text |Cite
|
Sign up to set email alerts
|

Individual- and group-level sex ratios under local mate competition: consequences of infanticide and reproductive dominance

Abstract: Extremely female-biased sex ratios of parasitoid wasps in multiple-foundress groups challenges evolutionary theory which predicts diminishing bias as foundress numbers increase. Recent theory based on foundress cooperation has achieved qualitative rather than quantitative success in explaining bias among parasitoids in the genus Sclerodermus. Here, we develop an explanation, expanding the theory of local mate competition, based on the observation that male production seems dominated by some foundresses within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…We found that sex ratios were extremely female biased. Although sex ratios varied according to brood size, the effect was not strong (as previously observed in S. brevicornis and many other members of the genus; Tang et al 2014 , Abdi et al 2020a , 2020 b , Guo et al 2022 , Lehtonen et al 2023 , Malabusini et al unpublished data).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…We found that sex ratios were extremely female biased. Although sex ratios varied according to brood size, the effect was not strong (as previously observed in S. brevicornis and many other members of the genus; Tang et al 2014 , Abdi et al 2020a , 2020 b , Guo et al 2022 , Lehtonen et al 2023 , Malabusini et al unpublished data).…”
Section: Discussionmentioning
confidence: 57%
“…In S. brevicornis , the duration of brood development is typically less than 1 month, depending on temperature, host species, and the number of contributing foundresses ( Lupi et al 2017 , Abdi et al 2021 ). The sex ratios of Sclerodermus broods are strongly female biased ( Abdi et al 2020a , 2020 b , 2021 , Malabusini et al 2022 , Lehtonen et al 2023 ). Males are the first offspring to mature (protandry), and they fertilize newly maturing females while they are still within their cocoons ( Hu et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%